Internet-based Control of Thermo-optical Plant Improvement based on the PID-GWO System - Shneen, Salam Waley; Alkhasraji, Jafaar M. Daif; Sulttan, Mohammed Q. (Journal of Fuzzy Systems and Control, 2024)
Experimental work systems with remote access to the laboratory are an inseparable part of engineering education at universities. Many important factors contribute to enhancing overall performance in terms of stability, reliability, and robustness. These include time responses, time delays, inverse responses, signiﬁcant nonlinearities, multivariable interactions, and modeling uncertainties. This work examines four scenarios for the thermo-optical plant: open-loop PID, a close-loop system without control, a close-loop with PID controller, and a close-loop with a Proportional-Integral-Derivative (PID) controller combined with Grey Wolf Optimizer (GWO), with the goal of achieving the optimal response for a remote thermo-optical plant. The results indicate that scenario four exhibits a smaller percentage overshoot compared to the other scenarios, thereby ensuring a larger stability margin. It outperforms the other three scenarios and signiﬁcantly enhances the system. The response speed demonstrates a greater percentage of improvement (74.05%).